Endpoint or Kinetic Measurement of Hydrogen Sulfide Production Capacity in Tissue Extracts - Hine, Christopher (Bio Protoc, 2017)
Hydrogen sulfide (H(2)S) gas is produced in cells and tissues via various enzymatic processes. H(2)S is an important signaling molecule in numerous biological processes, and deficiencies in endogenous H(2)S production are linked to cardiovascular and other health complications. Quantitation of steady-state H(2)S levels is challenging due to volatility of the gas and the need for specialized equipment. However, the capacity of an organ or tissue extract to produce H(2)S under optimized reaction conditions can be measured by a number of current assays that vary in sensitivity, specificity and throughput capacity. We developed a rapid, inexpensive, specific and relatively high-throughput method for quantitative detection of H(2)S production capacity from biological tissues. H(2)S released into the head space above a biological sample reacts with lead acetate to form lead sulfide, which is measured on a continuous basis using a plate reader or as an endpoint assay.